Assessment of the Sustainability Level of Wonosari Tea Agrotourism in Malang Regency Using the Multidimensional Scaling (MDS) Method Through the Rapid Appraisal for Agrotourism (RAP-Agrotourism) Approach: Penilaian Tingkat Keberlanjutan Agrowisata Teh Wonosari di Kabupaten Malang dengan Metode Multidimensional Scaling (MDS) Melalui Pendekatan Rapid Appraisal for Agrotourism (RAP-Agrotourism) - Resta Feby Arini; Dona Wahyuning Laily; Prasmita Dian Wijayati (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
Wonosari Tea Agrotourism is a plantation-based tourist destination in Malang Regency with considerable potential, yet it faces multidimensional management challenges. Domestic tourist visits during 2016–2025 fluctuated significantly, indicating management dynamics and potential pressures on the area's long-term viability. Ecological, economic, socio-cultural, infrastructure, and institutional pressures may also affect sustainability. This study aimed to analyze the sustainability status of Wonosari Tea Agrotourism using the Multidimensional Scaling (MDS) method through the Rapid Appraisal for Agrotourism (Rap-Agrotourism) approach. Data were collected through interviews and questionnaires involving managers and visitors across five dimensions, each with six attributes. Results showed that the overall sustainability index reached 72.88, categorized as moderately sustainable. The ecological (77.13), socio-cultural (79.13), and institutional (91.02) dimensions were classified as sustainable, while infrastructure (67.22) was moderately sustainable. The economic dimension obtained the lowest score (49.88) and was categorized as less sustainable, making it the primary priority for improvement. Sensitive attributes in the economic dimension include ticket and product pricing and tea product processing. Therefore, agrotourism management should focus on strengthening the economic dimension through optimizing these sensitive attributes to support overall sustainability and enhance the long-term viability of the area.